Diagenetic Evolution and its Link to Poroperm Development in Paleozoic Carbonates of Cat Ba Island in Northeast Vietnam - Dieu Nguyen, Ly Thi (Bulletin of Earth Sciences of Thailand, 2021)
The study focuses on the diagenetic development of Paleozoic carbonate rocks on the Cat Ba island-Northeast Vietnam, via the integration of outcrop study, especially fracture cements, and isotopic analysis. From the C-O isotope plot, there are two distinct trends: 1) burial trend and 2) meteoric mixing trend. Paleozoic limestone in Cat Ba island experienced a consistent set of burial re-equilibration processes preserving remnants of a very early stage of burial, until the oxygen isotope values of veins and matrix calcites reached around -12‰. Around this value, the permeability of matrix is lost. The rocks can be later fractured to create pathways for fluid during uplift or subsequent deformations. Most fractures formed after the loss of matrix permeability are linked to Tertiary strike-slip displacement, which created three main fracture orientations: NE-SW, NW-SE and NNE-SSW. A meteoric mixing trend is preserved in calcites cement infilling in these fractures and their associated speleothems. Their isotope plot outlines two groups: 1) flowstones precipitated from bicarbonate-rich water coming from dissolved limestone at depth; 2) precipitation from fluid-dominant soil waters, which indicates the influence of shallow meteoric groundwater supplying most of the bicarbonate ions (Moore, 2001). When compared with a similar study of outcrops in Thuy Nguyen district (80 km away), the results show similar trends, which indicates potential regional application. Techniques used in this studies can be combined with other conventional reservoir characterization techniques to better understand diagenesis-related poroperm development in carbonate basement play, especially in the Gulf of Tonkin.